An experiment of predicting Total Electron Content (TEC) by fuzzy inference systems - Akyilmaz, O.; Arslan, N. (SPRINGER, 2008)
The Total Electron Content (TEC) is predicted by fuzzy inference systems for various station-satellite pairs. GPS data from the GRAZ, HFLK, LINZ, MOPI and UZHL permanent stations are processed in order to obtain the vertical total electron content (VTEC) using differenced carrier-smoothed code observations. The quality of the VTEC prediction was studied on 9 and 11 September 2005 (DOY 252 and 254). The predictions were computed for 5, 10 and 15 min intervals. The mean accuracies of predictions are about 0.1, 0.2 and 0.3 TECU for these time intervals. More than 98% of the VTEC is successfully recovered with the proposed prediction method.
Keywords: GPS; ionosphere; VTEC; prediction; Geology